Novel SARS-CoV-2 Variant in Travelers from Brazil to Japan - Fujino, Takahisa; Nomoto, Hidetoshi; Kutsuna, Satoshi; Ujiie, Mugen; Suzuki, Tetsuya; Sato, Rubuna; Fujimoto, Tsuguto; Kuroda, Makoto; Wakita, Takaji; Ohmagari, Norio (Emerging infectious diseases, 2021)
Multiple severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with higher transmission potential have been emerging globally, including SARS-CoV-2 variants from the United Kingdom and South Africa. We report 4 travelers from Brazil to Japan in January 2021 infected with a novel SARS-CoV-2 variant with an additional set of mutations.